Systematic Review Of Scratch As A Media For Teaching Computational Thinking In Mathematics - Nurhidayat, Indra; Sukjaya Kusumah, Yaya (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The use of Scratch software has become the focus of research in the context of mathematics learning. This study focuses on analyzing the effect of using Scratch on students' computational thinking skills. Methods This research uses the SLR (Systematic Literature Review) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) for the topics of Computational Thinking (CT) and Scratch media.   The literature search was carried out thoroughly and systematically using various academic databases, namely Erick Jurnal. Research shows that the use of Scratch is effective in improving students' CT skills, especially when integrated into various subjects, one of that mathematics. Integrating Scratch is also effective in improving students' CT skills in elementary level, more effective with another approach like m-block, python, STEAM, and VEE. Next deep research is needed to support CT learning through Scratch programming.